CODING LOGICAL MECHANISM AND STEREOTYPING IN GENDER CYBER HUMORS - Truly Almendo Pasaribu; A. Effendi Kadarisman (Soegijapranata Catholic University, 2016)
Gender-related humors have their own way of being funny; and this research aims to find out how and why they are funny. For this purpose, both researchers have collected 50 gender cyber humors and analyzed them, first, to decode how their logical mechanism relates to specific linguistic features, and secondly, to uncover how gender stereotyping contributes to the comical effects. The twisting of logic and linguistic ambiguity is analyzed formally using Attardos (2001) General Theory of Verbal Humor (GTVH) and supported by gender studies. The findings reveal that the logical mechanism consists of elements of incongruities, and gender stereotyping presents negative stereotypical images. The analysis further shows that some gender stereotypical images ridicule traditional roles of man and woman while others make fun of non-traditional representations. This shift from women only to both men and women as targets of gender humors has been an impact of effective feminist movements.